ABU ALI IBN SINO'S SCIENTIFIC LEGACY AND ITS RELEVANCE WITH TODAY'S MEDICINE (The New Uzbekistan Journal of Medicine, 2025)
The article provides information on the reforms implemented in the medical sector of Uzbekistan and the importance of medical scientific heritage. Changes in medical knowledge and the importance of international cooperation in this area are noted. Scientifically based information will also be provided on the "Canons of Medicine" of Abu Ali ibn Sino, which left a huge legacy to world medical science, and their significance today.